OPTIMASI PENERIMAAN SELEKSI HIBAH AKADEMIS DI SMA NEGERI 1 LIMA PULUH DENGAN METODE WP - DIMAS PRATAMA; Jeperson Hutahaean; Andri Nata (LPPM Universitas Abdurrab, 2026)
The selection process for academic grant recipients at SMA Negeri 1 Lima Puluh has been conducted manually, which may lead to inaccurate targeting, lack of objectivity, and longer decision-making time. This study aims to optimize the selection process of academic grant recipients by implementing a decision support system using the Weighted Product (WP) method. The WP method was chosen because it can rank alternatives based on preference values derived from several predetermined criteria, such as academic scores, family economic conditions, student achievements, and the number of family dependents. As for the number of alternatives, there are 15 alternatives, including Nazwa Ayundra (A1), Nur Ayudira (A2), Rangga Pramana (A3), Ratna Ajiya Gea (A4), Nachaysa Asita (A5), Luthfi (A6), Naysila Aulia Izati (A7), Nurannisa Adha (A8), Nur Jana Sakillah (A9), Nur Ilham Syalahudin Ginting (A10), Nurul Huda Ikhsan (A11), Punchani Rizky Simbolon (A12), Rahayu (A13), Rama Dhani Reno Franstyo (A14), Rizky Hamdani (A15), Reno Franstyo (A16), and Rizky Hamdani (A17). The research method includes data collection, system requirements analysis, system design, and the implementation of the WP method in the calculation and ranking process of grant candidates. The results show that the implementation of the WP method can assist the school in conducting the selection process in a more systematic, objective, and transparent manner. The designed system is also able to generate recommendations for academic grant recipients more quickly and accurately based on the highest preference values. Therefore, it can be concluded that the application of the WP method in a decision support system can improve the effectiveness and accuracy of the selection process for academic grant recipients at SMA Negeri 1 Lima Puluh.